Of the Analysis of Emotional Strain Psychological Classification - Sayyora Xashimova Khalmurodovna (Periodica Journal, 2022)
This article examines the psychological nature and classification of emotional tension in adolescent students with disabilities. Also, the psychological characteristics that affect emotional tension and specific methods for eliminating this factor have been illuminated through modern research
Keywords: eliminating; characteristics; emotional; tension